Māori Architecture 1900–18 - McKay, Bill; Walmsley, Antonia (Architectural History Aotearoa, 2004)
This decade can be noted for several distinct approaches to Māori architecture, reflecting a variety of nationalistic impulses. This paper offers a brief overview of the diversity of Māori architecture and ideas in this period. Pākehā, in the search for national identity, and also reflecting the interests of the global Arts and Crafts movement, were enthused by the local example of the carved and decorated whare whakairo, native timbers, Māori adzing techniques and local flora and fauna. This can be seen in the work of architects such as JW Chapman Taylor, as well as the symbolism and trademarks of popular culture, and the pattern of museum acquisitions. By the twentieth century Māori were seen as a culture that could soon become extinct and this is reflected in the images of artists such as Goldie ("The Calm Close of Valour’s Various Days"), Lindauer’s interest in preserving ersatz records of tradition and custom, and Dittmer’s interest in myth and legend. Parliamentarian Āpirana Ngata, a member of the Young Maori Party, was very influential in the revival of certain customary arts (seen in the later establishment of schools of Māori arts and crafts in Rotorua) but he and his colleagues promoted a form of these arts that while "encouraging national Maori unity" also suppressed the diversity of activity in modern figurative painting and tribal identity for instance. These approaches can be contrasted with the patterns of building by other Māori movements more opposed to the government and actively seeking the restoration of Māori lands, rights and mana. Rua Kēnana’s settlement at Maungapōhatu in the 1910s and TW Rātana’s hall and church building later in the century (his ministry began in 1918) eschew the use of any meeting house forms or customary motifs – they were turning to new forms and symbols to sustain Māori identity in the new century.